MAUS TRATOS NA INFÂNCIA E ADOLESCÊNCIA: PROTOCOLO DE ATENDIMENTO NO CONSULTÓRIO ODONTOLÓGICO - Bohner, Lauren Oliveira Lima; Bohner, Tanny Oliveira Lima; Canto, Graziela de Luca (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611703912 Child and teenager mistreatment occur when an individual commits an act, which is able toinduce physical, psychological or sexual violence, against the victim wishes and that may cause serious consequences, such as permanent injuries and psychosocial problems. Severe injuries,usually in young children, which are not justified by the explanation given by the parents, may beevidence of mistreatment. Bruises, lacerations, fractures and burns are the main warning signs ofdomestic violence. The frequent involvement of areas, like the face structure and oral cavitymakes the surgeon - dentist able to diagnose the occurrence of such events. According to theMinistry of Health, it is required compulsory notification of violence cases by health professionalswho attend by SUS. This action aims to stop violent attitudes and abuser behaviors. Abuse casesare difficult to diagnose because of its complexity, involving psychological, behavioral, social andfiscal factors. Often, unfortunately, the dentist has no capacity to make a correct diagnostic andmake the necessary referral. The objective of this study is to review the actions against childrenand adolescents violence that must be taken by the dentist, in order to become able todiagnosticate and perform against mistreatment suspicions, decreasing the prevalence ofrecurrent cases.